Effectiveness of Diarvis-BMD in Managing Educational Infrastructure Data - Karina Karina; Siti Nur Asifa; Suryadi Suryadi (Tarbawi: Jurnal Keilmuan Manajemen Pendidikan, 2025)
This study aims to determine the effectiveness of the Diarvis-BMD application in managing data related to educational facilities and infrastructure. The study uses a descriptive qualitative method, with data collection techniques including interviews, observation, and documentation. The interviews were conducted indirectly, meaning the interaction between the interviewer and the respondents took place through an intermediary, using a Google Form containing questions related to the use of the application. Documentation consisted of application screenshots. This study involved four elementary school operators in the Margaasih District, Bandung Regency. The findings show that the Diarvis application received positive evaluations from most users, particularly regarding efficiency, ease of use, and report generation. The study concludes that the Diarvis application has great potential to improve facility and infrastructure data management effectiveness in educational institutions. With continuous development, this application can become an optimal solution for modern and integrated educational facility management.